2017
DOI: 10.1055/s-0042-122960
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for early gastric cancer in very elderly patients age 85 or older

Abstract: Background and study aims The safety and efficacy of endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) in very elderly patients remains unclear. The aim of this study was to evaluate the safety and efficacy of ESD for EGC in patients age 85 years and older. Patients and methods Patients who underwent ESD for EGC between September 2003 and April 2015 were divided into 3 groups: the very elderly (≥ 85 years; 43 patients), the elderly (65 – 84 years; 511 patients), and the non-elderly ( ≤ 64 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…Most pEGCs were located in the gastric antrum (60/135, 44.4%) ( Table 2). The median size of pEGCs was 20 mm (interquartile range [IQR], [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and this was larger in the expanded criteria (30 mm; IQR, 25-40) and outside criteria groups (30 mm; IQR, 20-50) versus the LGD LGD was commonly located in the antrum (24/42, 57.1%). The most common morphology of pEGC was Paris 0-IIa (54/135, 40.0%).…”
Section: Lesion Assessmentmentioning
confidence: 99%
“…Most pEGCs were located in the gastric antrum (60/135, 44.4%) ( Table 2). The median size of pEGCs was 20 mm (interquartile range [IQR], [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and this was larger in the expanded criteria (30 mm; IQR, 25-40) and outside criteria groups (30 mm; IQR, 20-50) versus the LGD LGD was commonly located in the antrum (24/42, 57.1%). The most common morphology of pEGC was Paris 0-IIa (54/135, 40.0%).…”
Section: Lesion Assessmentmentioning
confidence: 99%
“…The mean life expectancy in Japan at the age of 85 years was reported to be 6 and 8 years for men and women, respectively . Although previous studies have reported that endoscopic resection of EGC can be carried out safely even in older patients, resection has not been shown to improve the prognosis of older patients . Therefore, as shown by the present patient, no treatment might be the appropriate strategy.…”
mentioning
confidence: 99%
“…Several studies have reported clinical outcomes of gastric ESD in elderly patients . A recent meta‐analysis also showed that gastric ESD in elderly patients appears to be a safe procedure, and the long‐term prognosis was acceptable with favorable outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…The extensive use of endoscopy has increased gastrointestinal cancer diagnosis at an early stage . As the elderly population increases, the proportion of elderly patients who will require endoscopic submucosal dissection (ESD) is expected to increase further.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation